Comparison of Continuous Infusion of Intravenous Tramadol and Fentanyl on Postoperative Analgesia in Cardiac Surgery - Kaneez Ume Farwa, Waseema Afzal, Shumaila Ali Rai, Taha Malik, Hafiz Haseeb Ahsan, Fatima Skina, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the efficacy between the fentanyl and tramadol infusion on post-operative cure of pain after a valvular heart surgery. Methods: Total of 40 patients were included in the study who underwent valvular heart surgery. Patients were divided into two groups, 20 patients were included in Tramadol group while 20 patients were assigned the Fentanyl group. After getting off from cardiopulmonary bypass pump (CPB), drug infusions were started. The drugs were continued for a duration of 48 hours after the surgery. The dose of Fentanyl was 0.5-1ug.kg-1.h-1 through continuous infusion for about 48 hours whereas Tramadol was given at a dose of 0.1-0.2 mg.kg- 1.h-1. Additionally, both the groups were also given intravenous paracetamol 1gm every 8 hours. Verbal rating scale comprising of 11 points was used to assess the efficacy of analgesia. The interval of data collection was 6h, 12h, 24h, 36h and 48h after surgery. Results: The mean cross clamping time, CPB time, mechanical ventilation, ICU stay and hospital stay of group F was 90.51±5.18 minutes, 120.65±5.58 minutes, 589.45±3.64 minutes, 4.01±0.45 days and 8.11±1.97 days, respectively. While, the mean cross clamping time, CPB time, mechanical ventilation time, ICU day and hospital days of group T was 86.91±4.11 minutes, 111.31±2.84 minutes, 507.45±5.54 minutes, 3.15±0.67 days and 7.4±1.14 days, respectively. The differences were statistically significant except hospital days (p=0.1777). Conclusion: It is evident from the given study that tramadol infusion is having equally analgesic characteristics as compared to fentanyl infusion after valvular heart surgery. Keywords: Cardiopulmonary bypass (CPB), Postoperative analgesia, Pain relief, assessment, Tramadol infusion.